Preparation method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater

By pretreating and hydrothermal reaction of the reel wastewater, nitrogen-doped carbon quantum dots were prepared, which solved the problems of reel wastewater treatment and utilization, and achieved efficient environmental governance and resource reuse.

CN119529829AActive Publication Date: 2025-02-28ANHUI AGRICULTURAL UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411717152.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat and utilize silk reeling wastewater, resulting in environmental pollution and waste of resources.

Method used

Nitrogen-doped carbon quantum dots with good stability and excellent luminescence properties were prepared by pretreatment of silk reel wastewater, hydrothermal reaction with amino acids, centrifugation, dialysis and drying.

Benefits of technology

It has achieved high purity synthesis of carbon quantum dots, has biocompatibility and excellent fluorescence characteristics, and can be used in fields such as biosensing and imaging, while reducing environmental pollution and resource consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529829A_ABST
    Figure CN119529829A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing nitrogen-doped carbon quantum dots based on reeling wastewater, which mainly comprises the steps of pretreatment of reeling wastewater, hydrothermal reaction of reeling wastewater and L-asparaginic acid, centrifugation, dialysis, drying treatment and the like to obtain nitrogen-doped carbon quantum dot solid powder. The nitrogen-doped carbon quantum dots prepared by the method are spherical, and the average diameter of the nitrogen-doped carbon quantum dots is about 9.8 nm; under ultraviolet excitation light, the nitrogen-doped carbon quantum dots obtained by the method emit blue-green fluorescence; the method is simple to operate, the fluorescence emission wavelength can be regulated and controlled based on nitrogen doping of amino acid, the emission wavelength is continuously increased along with the increase of the nitrogen content, and the fluorescence wavelength is subjected to red shift; based on the preparation technology provided by the invention, not only is the problem of reutilization of reeling wastewater solved, but also the prepared nitrogen-doped carbon quantum dots have potential application prospects in multiple fields such as biomedicine, energy, environment, electronic information, textile and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation, and in particular relates to a method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater. Background Art

[0002] my country's silk reeling technology has long been in the world's leading position and has made great contributions to the development of the world's sericulture industry. However, the pollution caused by the reeling wastewater generated in the reeling process to the environment cannot be underestimated. From the perspective of the process flow, the reeling wastewater is mainly composed of three parts: cocoon boiling, vertical reeling (reeling and re-shaking), and wastewater from by-products. Its main pollutants are organic matter such as sericin, fibroin, pupa protein, fatty acids, etc., especially the by-product processing wastewater contains a very high concentration of organic matter. Reeling wastewater is an organic wastewater with a high content of nitrogen and phosphorus. If it is directly discharged into rivers, lakes and seas, it will not only cause a sharp increase in COD and BOD of the water body, causing hazards such as eutrophication, but also cause waste of resources such as sericin.

[0003] At present, the common silk reeling wastewater treatment technologies mainly include physical and chemical treatment technology, anaerobic biological treatment technology, sequential batch activated sludge process (SBR) treatment process, aerated biological filter (BAF) treatment process, etc. The main advantage of using physical and chemical treatment technology is that the effluent water quality is relatively stable, but the investment cost is high, the energy consumption is high, and it is easy to cause secondary pollution; anaerobic biological treatment technology has many advantages, such as low power consumption, less residual sludge, and can degrade some organic matter that is not easy to degrade, but the start-up time of anaerobic organisms is long, and anaerobic microbial flora needs to be cultivated and domesticated, which is very demanding on operation and The management requirements are high. After SBR biochemical treatment, most of the chemical oxygen demand and biochemical oxygen demand in the silk reeling wastewater will be degraded, and part of the ammonia nitrogen will be denitrified, with good purification effect, but the automation control and drainage equipment requirements are high, the post-treatment equipment requirements are large, and the head loss is large. After BAF biochemical treatment, most of the BOD and COD are effectively degraded, and part of the ammonia nitrogen undergoes nitrification under aerobic conditions, but the BAF process cannot achieve the function of biological phosphorus removal, and can only be combined with chemical phosphorus removal to achieve phosphorus removal, and the influent water quality requirements are high, and the repeated flushing operation is complicated. Therefore, the development of a method for treating and reusing silk reeling wastewater is of great significance to reducing the discharge of silk reeling wastewater and reducing environmental pollution.

[0004] As a new type of carbon-based nanomaterial, carbon quantum dots have potential application prospects in the fields of biological imaging, sensing and catalysis due to their excellent biocompatibility, water solubility and chemical stability. At present, the preparation of carbon quantum dots based on biomass waste materials has attracted widespread attention. Researchers have converted biomass waste materials such as gardening waste, kitchen waste, agricultural and forestry waste (bagasse, waste bean dregs, etc.) into high-performance carbon quantum dots through simple chemical or biological methods. This carbon quantum dot prepared from biomass waste materials not only has good biocompatibility and excellent fluorescence properties, can be used for biosensing, imaging, photovoltaic cells and other energy applications, but also can realize the recycling of waste and reduce environmental pollution. Therefore, seeking a technology to convert silk reeling wastewater into carbon quantum dots can not only reduce the discharge of silk reeling wastewater, but also realize the high-value utilization of silk reeling wastewater, which is of great significance to the realization of sustainable development of society. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing carbon quantum dots based on silk reeling wastewater, thereby achieving the purpose of the invention of preparing nitrogen-doped carbon quantum dots with good stability and excellent luminescence performance.

[0006] In order to solve the above technical problems, the object of the present invention is to provide a preparation method of nitrogen-doped carbon quantum dots based on silk reeling wastewater, characterized in that the preparation method comprises pretreatment of silk reeling wastewater, hydrothermal reaction of silk reeling wastewater with amino acids, centrifugation, dialysis and drying treatment:

[0007] The silk reeling wastewater pretreatment is to remove floating matter, suspended matter and some large particle impurities in the silk reeling wastewater;

[0008] The hydrothermal reaction of the silk reeling wastewater and amino acid comprises the following steps:

[0009] Step 1: Prepare sodium hydroxide solutions of different concentrations;

[0010] Step 2: mixing the pretreated silk reeling wastewater with the sodium hydroxide solution in step 1 in a certain proportion to obtain a mixed solution, and transferring the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor;

[0011] Step 3: adding a certain mass of amino acids to the mixed solution described in step 2, dissolving them to obtain a reaction solution, sealing the stainless steel reactor, heating it for hydrothermal reaction, and obtaining a solution after hydrothermal reaction;

[0012] The centrifugation, dialysis and drying treatment, the solution after the hydrothermal reaction obtained in step 3 is cooled and centrifuged to obtain a supernatant containing carbon quantum dots, the supernatant is placed in a dialysis bag for dialysis, and the dialyzed supernatant is dried to obtain a carbon quantum dot solid powder.

[0013] Furthermore, in step 1, the concentration of the sodium hydroxide solution is 0.8 mol / L to 1 mol / L.

[0014] Furthermore, in step 2, the mass ratio of the reeling wastewater and the sodium hydroxide solution is 1:1 to 1:2.

[0015] Preferably, in step 3, the amino acid in the reaction solution is one or more of L-aspartic acid, histidine, arginine and lysine.

[0016] Preferably, in step 3, the amino acid in the reaction solution is L-aspartic acid, with a mass fraction of 0.1% to 0.5%.

[0017] Furthermore, the heating reaction temperature of the hydrothermal reaction in step 3 is 190-250°C.

[0018] Furthermore, the reaction time of the heating reaction in step 3 is 4 to 8 hours.

[0019] Furthermore, in S3, the molecular weight cut-off of the dialysis bag is 1000.

[0020] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are:

[0021] 1. The hydrothermal method is a green chemical synthesis method. During the hydrothermal reaction, phosphorus is directly converted or doped into carbon quantum dots, which can achieve the function of biological phosphorus removal without the use of harmful organic solvents, reducing environmental pollution and resource consumption.

[0022] 2. The hydrothermal method can be used to synthesize carbon quantum dots, which can produce high-purity carbon quantum dots in a shorter time and improve the synthesis efficiency of carbon quantum dots.

[0023] 3. Amino acids are used as nitrogen sources, especially L-aspartic acid, which is an amino acid with good biocompatibility. More nitrogen atoms can be introduced during the synthesis of carbon quantum dots, thereby changing the electronic structure of carbon quantum dots and regulating their optical properties. The synthetic precursor of L-aspartic acid can not only realize nitrogen doping of carbon quantum dots and adjust the fluorescence intensity of carbon quantum dots, but also adjust the fluorescence emission wavelength, which is of great significance to expanding the application of carbon quantum dots.

[0024] 4. Based on the preparation method of the present invention, the reuse technology of silk reeling wastewater can be enriched, which can not only reduce the discharge of silk reeling wastewater and reduce environmental pollution, but also realize the high-value utilization of silk reeling wastewater, which is of great significance to achieving sustainable social development. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the preparation process of carbon quantum dots based on silk reeling wastewater.

[0026] Figure 2 (ab) Transmission electron microscopy (TEM) images of carbon quantum dots at different magnifications (c) Corresponding particle size distribution diagram of carbon quantum dots.

[0027] Figure 3 Infrared spectra of carbon quantum dots obtained under different synthesis conditions.

[0028] Figure 4 Dynamic light scattering test data of carbon quantum dot solutions obtained at different hydrothermal times.

[0029] Figure 5 Dynamic light scattering test data of carbon quantum dot solutions obtained with different sodium hydroxide concentrations.

[0030] Figure 6 This is a dynamic light scattering test data diagram of the carbon quantum dot solution obtained at different mass fractions of L-aspartic acid.

[0031] Figure 7 (a) Excitation spectra of carbon quantum dots obtained at different hydrothermal times; (b) Emission spectra of carbon quantum dots obtained at different hydrothermal times; (c) Color comparison of carbon quantum dots dispersed in water obtained at different hydrothermal times under sunlight, from left to right, 4h, 5h, 6h, 7h, 8h; (d) Color comparison of carbon quantum dots dispersed in water obtained at different hydrothermal times under ultraviolet light, from left to right, 4h, 5h, 6h, 7h, 8h.

[0032] Figure 8 (a) Excitation spectra of carbon quantum dots obtained at different sodium hydroxide concentrations; (b) Emission spectra of carbon quantum dots obtained at different sodium hydroxide concentrations; (c) Color comparison of carbon quantum dots dispersed in water obtained at different sodium hydroxide concentrations under sunlight, from left to right, 0.1M, 0.2M, 0.4M, 0.6M, 0.8M; (d) Color comparison of carbon quantum dots dispersed in water obtained at different sodium hydroxide concentrations under ultraviolet light, from left to right, 0.1M, 0.2M, 0.4M, 0.6M, 0.8M.

[0033] Fig. 9(a) Excitation spectra of carbon quantum dots obtained at different L-aspartic acid mass fractions; (b) Emission spectra of carbon quantum dot solutions obtained at different L-aspartic acid mass fractions; (c) Color comparison of carbon quantum dots dispersed in water at different L-aspartic acid mass fractions under sunlight, from left to right, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%; (d) Color comparison of carbon quantum dots dispersed in water at different L-aspartic acid mass fractions under ultraviolet light under sunlight, from left to right, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%.

[0034] Fig.10 (a) Ultraviolet absorption spectra of the prepared carbon quantum dots dispersed in buffer solutions of different pH values; (b) Emission spectra of the prepared carbon quantum dots dispersed in buffer solutions of different pH values; (c) Color comparison of the prepared carbon quantum dots dispersed in buffer solutions of different pH values ​​under sunlight, from left to right, pH=2 to pH=12; (d) Color comparison of the prepared carbon quantum dots dispersed in buffer solutions of different pH values ​​under ultraviolet light. DETAILED DESCRIPTION

[0035] The following is a detailed description of the embodiments and the attached Figure 1-10 , further illustrating the present invention.

[0036] Example 1 A method for preparing carbon quantum dots based on silk reeling wastewater

[0037] S1. First, assemble the vacuum filtration device, connect the vacuum pump to the filtration bottle, then take a piece of polytetrafluoroethylene microporous filter membrane and place it in the Buchner funnel, use the filter membrane to cover all the micropores in the Buchner funnel, then turn on the vacuum pump switch of the filtration device, then pour the silk reeling wastewater into the funnel, and use the filter membrane to filter out floating matter, suspended matter and some large particle impurities in the silk reeling wastewater, so as to obtain the pretreated silk reeling wastewater.

[0038] S2. Weigh 0.08g of sodium hydroxide powder, pour it into 20mL of deionized water, stir with a glass rod to fully dissolve the sodium hydroxide, and obtain a sodium hydroxide solution with a concentration of 0.1mol / L. Then use a measuring cylinder to measure 20mL of filtered silk reeling wastewater and pour it into the sodium hydroxide solution, and use a magnetic stirrer to fully mix the silk reeling wastewater and the sodium hydroxide solution.

[0039] S3, transfer 40mL of the evenly mixed sodium hydroxide and reeling solution to a stainless steel reactor lined with polytetrafluoroethylene, then add 40mg (mass fraction 0.1%) of L-aspartic acid, and then use a magnetic stirrer to fully dissolve the L-aspartic acid in the above mixed solution. Then seal the reactor and put it in an oven, the heating temperature of the oven is set at 190°C, stop heating after heating reaction for 6h, and let the reactor cool naturally to room temperature.

[0040] S4. Pour the solution in the reactor that has been naturally cooled to room temperature into the inner tube of a centrifuge, and centrifuge it at a speed of 12,000 r / min for 15 minutes to remove non-fluorescent precipitates and obtain a supernatant of carbon quantum dots.

[0041] S5. Pour the supernatant after centrifugation into a dialysis bag with a molecular weight cutoff of 1000, place it in deionized water for 24 hours to remove residual sodium hydroxide, and finally place the dialyzed solution in a vacuum drying oven at 40°C to obtain a carbon quantum dot solid powder.

[0042] Example 2 A method for preparing carbon quantum dots based on silk reeling wastewater

[0043] The difference between this embodiment and embodiment 1 is that the concentration of sodium hydroxide in step S2 is 0.2 mol / L.

[0044] Example 3 A method for preparing carbon quantum dots based on silk reeling wastewater

[0045] The difference between this embodiment and embodiment 1 is that the concentration of sodium hydroxide in step S2 is 0.4 mol / L.

[0046] Example 4 A method for preparing carbon quantum dots based on silk reeling wastewater

[0047] The difference between this embodiment and embodiment 1 is that the concentration of sodium hydroxide in step S2 is 0.6 mol / L.

[0048] Example 5 A method for preparing carbon quantum dots based on silk reeling wastewater

[0049] The difference between this embodiment and embodiment 1 is that the concentration of sodium hydroxide in step S2 is 0.8 mol / L.

[0050] Example 6 A method for preparing carbon quantum dots based on silk reeling wastewater

[0051] The difference between this embodiment and embodiment 1 is that the heating reaction time in step S3 is 4 hours.

[0052] Example 7 A method for preparing carbon quantum dots based on silk reeling wastewater

[0053] The difference between this embodiment and embodiment 1 is that the heating reaction time in step S3 is 5 hours.

[0054] Example 8 A method for preparing carbon quantum dots based on silk reeling wastewater

[0055] The difference between this embodiment and embodiment 1 is that the heating reaction time in step S3 is 7 hours.

[0056] Example 9 A method for preparing carbon quantum dots based on silk reeling wastewater

[0057] The difference between this embodiment and embodiment 1 is that the heating reaction time in step S3 is 8 hours.

[0058] Example 10 A method for preparing carbon quantum dots based on silk reeling wastewater

[0059] The difference between this embodiment and embodiment 1 is that the amount of L-aspartic acid added in step S3 is 80 mg (mass fraction 0.2%).

[0060] Example 11 A method for preparing carbon quantum dots based on silk reeling wastewater

[0061] The difference between this embodiment and embodiment 1 is that the amount of L-aspartic acid added in step S3 is 120 mg (mass fraction 0.3%).

[0062] Example 12 A method for preparing carbon quantum dots based on silk reeling wastewater

[0063] The difference between this embodiment and embodiment 1 is that the amount of L-aspartic acid added in step S3 is 160 mg (mass fraction 0.4%).

[0064] Example 13 A method for preparing carbon quantum dots based on silk reeling wastewater

[0065] The difference between this embodiment and embodiment 1 is that the amount of L-aspartic acid added in step S3 is 200 mg (mass fraction 0.5%).

[0066] The concentration of sodium hydroxide in step S2 in Examples 1-5, the hydrothermal reaction time in step S3 in Examples 6-9, and the mass fraction of L-aspartic acid in step S3 in Examples 10-13 will all affect the structural characteristics of carbon quantum dots, the dynamic light scattering of carbon quantum dot solutions, and the luminescence properties of carbon quantum dots.

[0067] Figure 2 (ab) are TEM images of carbon quantum dots obtained by hydrothermal heating in 0.1 M sodium hydroxide for 6 h at different magnifications. From the TEM results, it can be seen that the synthesized carbon quantum dots are composed of dispersed spherical carbon particles. Figure 2 (c) is the particle size distribution of the corresponding carbon quantum dots. From the distribution diagram, it can be seen that the particle size of the carbon quantum dots is about 5nm-16nm, the average diameter is about 9.8nm, and the size distribution is uniform.

[0068] Figure 3 The infrared absorption spectra of carbon quantum dots obtained under different conditions are shown in Figure 1. When the hydrothermal reaction conditions are 5 hours and the sodium hydroxide concentration is 0.1 M, the infrared absorption spectrum of carbon quantum dots prepared shows a wave number of 1558 cm -1 The absorption peak at is due to the skeleton vibration of C=C; the wave number is 1491cm -1 The absorption peak is also caused by the skeleton vibration of C=C; the wave number is 1409cm -1 The absorption peak at corresponds to the bending vibration of CH-CH2; the wave number is 1258cm- 1 The absorption peak corresponds to the stretching vibration of CO, which can also be attributed to the bending vibration of CH. The wave number is 2359cm -1 The peak value corresponds to the cumulative double bond stretching vibration region of C≡C. When the hydrothermal time increases to 6h, the wave number is 2359cm -1 The peak disappears. After the reaction time increases, the structure of the carbon quantum dots changes, so the peak shifts slightly. Under the hydrothermal condition of 6h, 0.1M, and then nitrogen doping, the wave number is 2358cm -1 The peaks appear, corresponding to the cumulative double bond stretching vibration region of C≡C. The wave number ranges from 1399 to 1420 cm -1 , which is the stretching vibration of CN. The results show that the carbon quantum dots have more nitrogen atoms, which should be the product of the hydrothermal decomposition of proteins in the silk reeling wastewater, making the carbon quantum dots have excellent water solubility.

[0069] Figure 4 It is the dynamic light scattering intensity curve of the carbon quantum dot solution obtained under different hydrothermal times. As can be seen from the figure, with the increase of the hydrothermal reaction time, the particle size of the carbon quantum dot solution obtained by hydrothermal first increases, then decreases, and then continues to increase. When the hydrothermal reaction time is short, the particle size distribution is narrower. Increasing the hydrothermal time will increase the size of the particle aggregates in the solution, and the particle size distribution will increase at the same time. This may be because when the reaction time is short, the hydrothermal reaction is not sufficient, carbonization does not occur completely, only a small amount of carbon quantum dots are synthesized, and the organic matter in the unreacted reeling wastewater is filtered out. At this time, the aggregate particle size distribution of the carbon quantum dots is relatively narrow. When the reaction time is extended, the organic matter in the reeling wastewater fully reacts with sodium hydroxide, and the hydrothermal kettle not only has a large number of carbon quantum dots, but also has residual impurities. The aggregate particle size in the solution increases and the distribution becomes wider.

[0070] like Figure 5It is the dynamic light scattering intensity curve of the carbon quantum dot solution obtained under different sodium hydroxide concentrations. As can be seen from the figure, with the increase of sodium hydroxide concentration, the particle size of the carbon quantum dot solution obtained by hydrothermal first increases and then decreases. Its particle size distribution gradually widens with the increase of sodium hydroxide concentration. The main reason is that when the sodium hydroxide concentration is low, the hydrothermal reaction is not sufficient, only a small amount of carbon quantum dots are synthesized, the unreacted organic matter is filtered out, and there are relatively few water-soluble impurities. Therefore, at this time, it is mainly carbon quantum dots and their aggregates, and the distribution at this time is also relatively narrow. When the sodium hydroxide concentration increases, the silk reacts more fully with sodium hydroxide, producing more carbon quantum dot aggregate particles and impurity particles with better dispersibility in water, so the size gradually increases.

[0071] like Figure 6 It is the dynamic light scattering intensity curve of the carbon quantum dot solution obtained under different aspartic acid addition amounts (different mass fractions). It can be seen from the figure that with the increase of aspartic acid addition amount, the particle size of the carbon quantum dot solution obtained by hydrothermal treatment shows a slow increasing trend. Its particle size distribution shows a trend of first decreasing and then increasing with the increase of aspartic acid addition amount. When the aspartic acid addition amount is low, aspartic acid directly hydrothermally generates aggregate particles with uneven size distribution. When the aspartic acid addition amount increases, aspartic acid is fully mixed with organic matter in the reeling wastewater to obtain uniform carbon quantum dot aggregate particles, and the distribution and size are significantly increased.

[0072] Figure 7 (a) is the excitation spectrum of carbon quantum dots obtained under different hydrothermal time. It can be seen from the figure that the excitation light position of carbon quantum dots obtained by hydrothermal reaction for 4h is located at 374nm, the excitation light position of carbon quantum obtained by 5h is located at 376nm, the excitation light position of carbon quantum obtained by 6h is located at 377nm, the excitation light position of carbon quantum obtained by 7h is located at 326nm, and the excitation light position of carbon quantum obtained by 8h is located at 325nm. With the increase of time, the excitation wavelength shows a trend of first increasing and then gradually decreasing. Figure 7(b) is the emission spectrum of carbon quantum dots obtained under different hydrothermal times. It can be seen from the figure that the emission position of carbon quantum dots obtained at 4h is located at 440nm, the emission position of carbon quantum dots obtained at 5h is located at 451nm, the emission position of carbon quantum dots obtained at 6h is located at 441nm, the emission position of carbon quantum dots obtained at 7h is located at 404nm, and the emission position of carbon quantum dots obtained at 8h is located at 403nm. The overall fluorescence emission peak shows a trend of first red shift and then blue shift, which corresponds to the trend of excitation wavelength change. In addition, with the increase of hydrothermal reaction time, the fluorescence intensity shows a trend of first decreasing and then increasing. When the hydrothermal reaction time is increased from 4 hours to 6 hours, the fluorescence intensity of the solution of carbon quantum dots continues to decrease, and from 6 hours to 7 hours, the fluorescence intensity of the solution of carbon quantum dots increases significantly. From 7 hours to 8 hours, the fluorescence intensity weakens again. Its fluorescence emission is mainly controlled by the quantum size effect. With the increase of reaction time, the size and number of carbon quantum dots continue to increase. This is because the carbon quantum dots are aggregated, causing their own quenching and resulting in reduced intensity.

[0073] Figure 7 c is the color comparison of carbon quantum dots under sunlight, from left to right, 4h, 5h, 6h, 7h, 8h. First, under sunlight, as the reaction time of the carbon quantum dot solution increases from 4 hours to 6 hours, the color of the solution changes from yellow to brownish yellow. As the reaction time continues to increase, the carbon quantum dot solution presents an inconspicuous light yellow or even transparent color. According to the principle of complementary colors, this trend change is consistent with the trend of the excitation light. Figure 7 d is the color contrast of the carbon quantum dot solution under ultraviolet light, which corresponds to the fluorescence emission wavelength of the solution. First, with the increase of reaction time, the emission wavelength increases. When the reaction time increases from 4 hours to 5 hours, the fluorescence wavelength red-shifts and appears blue-green under ultraviolet light. When the reaction time is long enough to 8 hours, the fluorescence emission wavelength shows an obvious blue shift. At this time, the emission wavelength is 403nm, and it appears blue under ultraviolet light.

[0074] Figure 8 (a) is the excitation spectrum of carbon quantum dots obtained under different sodium hydroxide concentrations. It can be seen from the figure that the excitation light position of carbon quantum dots obtained at 0.1mol / L is located at 368nm, the excitation light position of carbon quantum dots obtained at 0.2mol / L is located at 367nm, the excitation light position of carbon quantum dots obtained at 0.4mol / L is located at 367nm, the excitation light position of carbon quantum dots obtained at 0.6mol / L is located at 366nm, and the excitation light position of carbon quantum dots obtained at 0.8mol / L is located at 368nm. With the increase of time, the excitation wavelength shows a trend of first decreasing and then increasing. Figure 8(b) is the emission spectrum of carbon quantum dots obtained under different hydrothermal times. It can be seen from the figure that the emission position of carbon quantum dots obtained at 0.1mol / L is located at 442nm, the emission position of carbon quantum dots obtained at 0.2mol / L is located at 441nm, the emission position of carbon quantum dots obtained at 0.4mol / L is located at 452nm, the emission position of carbon quantum dots obtained at 0.6mol / L is located at 446nm, and the emission position of carbon quantum dots obtained at 0.8mol / L is located at 461nm. The overall fluorescence emission peak shows a trend of blue shift first and then red shift, which corresponds to the trend of excitation wavelength change. In addition, with the increase of particle concentration, the fluorescence intensity shows a trend of gradually decreasing. This is because the increase of carbon quantum dot particle concentration, the distance between particles is reduced, and they interact with each other, inhibiting the luminescence behavior of a single quantum dot, increasing the possibility of energy quenching, and superposition of carbon quantum dots at high concentrations, causing aggregation-induced quenching, and weakening fluorescence intensity.

[0075] Figure 8 (c) is the color comparison of carbon quantum dots under sunlight, from left to right, 0.1mol / L, 0.2mol / L, 0.4mol / L, 0.6mol / L, 0.8mol / L. First, under sunlight, the color of the carbon quantum dot solution changes from brown to light when the sodium hydroxide concentration increases from 0.1mol / L to 0.6mol / L, and then it continues to increase to 0.8mol / L, and then the color becomes darker. According to the principle of complementary colors, this trend change is consistent with the change trend of the excitation light. Fig. 9 (d) is the color contrast of the carbon quantum dot solution under ultraviolet light, which corresponds to the fluorescence emission wavelength of the solution. First, with the increase of concentration, the emission wavelength first decreases and then increases. When the reaction concentration increases from 0.1mol / L to 0.2mol / L, the fluorescence wavelength blue-shifts and appears blue light under ultraviolet light. When the reaction concentration reaches 0.8mol / L, the fluorescence emission wavelength shows an obvious red shift. At this time, the emission wavelength is 461nm, and it shows obvious blue-green light under ultraviolet light.

[0076] Fig. 9 (a) is the excitation spectrum of carbon quantum dots obtained by adding different amounts of L-aspartic acid (mass fraction). It can be seen from the figure that the excitation light position of carbon quantum dots obtained by 40mg (0.1%) is located at 360nm, the excitation light position of carbon quantum dots obtained by 80mg (0.2%) is located at 365nm, the excitation light position of carbon quantum dots obtained by 120mg (0.3%) is located at 365nm, the excitation light position of carbon quantum dots obtained by 160mg (0.4%) is located at 368nm, and the excitation light position of carbon quantum dots obtained by 200mg (0.5%) is located at 370nm. With the increase of time, the excitation wavelength shows a trend of gradually increasing. Fig. 9(b) is the emission spectrum of carbon quantum dots obtained at different hydrothermal times. It can be seen from the figure that the emission position of carbon quantum dots obtained by 40mg (0.1%) is located at 448nm, the emission position of carbon quantum dots obtained by 80mg (0.2%) is located at 450nm, the emission position of carbon quantum dots obtained by 120mg (0.3%) is located at 452nm, the emission position of carbon quantum dots obtained by 160mg (0.4%) is located at 455nm, and the emission position of carbon quantum dots obtained by 200mg (0.1%) is located at 460nm. The overall fluorescence emission peak shows a red-shift trend, which may be caused by different emission sites on the surface of carbon dots or uneven particle size distribution, corresponding to the trend of excitation wavelength change. In addition, with the increase of nitrogen doping, the fluorescence intensity shows a trend of continuous increase. This is because with the increase of nitrogen content, the transition energy gap in carbon quantum dots increases, the chemical stability and resistance to light decomposition are improved, especially when a certain nitrogen content is reached, the fluorescence intensity increases rapidly.

[0077] Fig. 9 (c) is the color comparison of carbon quantum dots under sunlight, from left to right, 40mg (0.1%), 80mg (0.2%), 120mg (0.3%), 160mg (0.4%), 200mg (0.5%). First, under sunlight, the color of the carbon quantum dot solution gradually darkens as the nitrogen content increases. According to the principle of complementary colors, this trend change is consistent with the trend of increasing excitation light. Fig. 9 (d) is the color comparison of the carbon quantum dot solution under ultraviolet light, which corresponds to the fluorescence emission wavelength of the solution. First, with the increase of nitrogen content, the emission wavelength continues to increase, and the fluorescence wavelength red-shifts, showing blue-green light under ultraviolet light.

[0078] Fig.10 (a) is the ultraviolet absorption spectrum of carbon quantum dots in different pH solutions. It can be seen from the figure that the position of the obtained ultraviolet light is located at 295nm, and the emission wavelength has not changed, indicating that the properties of carbon quantum dots in different pH buffer solutions have not changed and are not affected by pH. Figure 11(b) is the emission spectrum of carbon quantum dots in different pH solutions. It can be seen from the figure that the position of the obtained emission light is located at 450nm. The fluorescence intensity shows a trend of first increasing and then decreasing with the change of pH. This is because the pH causes the carbon quantum dots to undergo different degrees of hydrolysis and aggregation. Under acidic conditions, the fluorescence intensity reaches the highest, and under alkaline conditions, the fluorescence intensity is the lowest. It may be because there are many amino groups on the nitrogen-doped surface, and alkaline substances will affect the charge of the surface groups. Fig.10(c) shows the color change of carbon quantum dots in a buffer solution with a pH of 2-12 under sunlight. As can be seen from the figure, there is no obvious change in color under different pH values ​​under sunlight, indicating that pH has no significant effect on the luminescence properties of carbon quantum dots. Figure (d) shows the color change of carbon quantum dots in a buffer solution with a pH of 2-12 under ultraviolet light, which corresponds to the change in emission wavelength, and the solution shows blue fluorescence.

[0079] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.

[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater, characterized in that: The preparation method comprises pretreatment of silk reeling wastewater, hydrothermal reaction of silk reeling wastewater with amino acid, centrifugation, dialysis and drying treatment: The silk reeling wastewater pretreatment is to remove floating matter, suspended matter and some large particle impurities in the silk reeling wastewater; The hydrothermal reaction of the silk reeling wastewater and amino acid comprises the following steps: Step 1: Prepare sodium hydroxide solutions of different concentrations; Step 2: mixing the pretreated silk reeling wastewater with the sodium hydroxide solution in step 1 in a certain proportion to obtain a mixed solution, and transferring the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor; Step 3: adding a certain mass of amino acids to the mixed solution described in step 2, dissolving them to obtain a reaction solution, sealing the stainless steel reactor, heating it for hydrothermal reaction, and obtaining a solution after hydrothermal reaction; The centrifugation, dialysis and drying treatment, the solution after the hydrothermal reaction obtained in step 3 is cooled and centrifuged to obtain a supernatant containing carbon quantum dots, the supernatant is placed in a dialysis bag for dialysis, and the dialyzed supernatant is dried to obtain a carbon quantum dot solid powder.

2. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: In step 1, the concentration of the sodium hydroxide solution is 0.8 mol / L to 1 mol / L.

3. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: In step 2, the mass ratio of the silk reeling wastewater and the sodium hydroxide solution is 1:1 to 1:

2.

4. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: In step 3, the amino acid in the reaction solution is one or more of L-aspartic acid, histidine, arginine, and lysine.

5. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 4, characterized in that: In step 3, the amino acid in the reaction solution is L-aspartic acid, with a mass fraction of 0.1% to 0.5%.

6. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: The heating reaction temperature of the hydrothermal reaction in step 3 is 190-250°C.

7. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: The reaction time of the heating reaction in step 3 is 4 to 8 hours.

8. The method for preparing nitrogen-doped carbon quantum dots based on silk reeling wastewater according to claim 1, characterized in that: The molecular weight cut-off of the dialysis bag is 1000.

Citation Information

Patent Citations

  • Preparation method for triangle-shaped fluorescent silk fibroin-carbon dot composite nanoparticle

    CN105012962A

  • Method for preparing carbon quantum dot labeled probe for silk fibroin extracted cell development

    CN105018082A

  • Nanocarbon dot or graphene quantum dot feeding type silkworm rearing method for preparing fluorescent silk and product

    CN106069992A

  • Nitrogen doped fluorescent carbon quantum dot and preparation method thereof

    CN108456519A

  • Multi-mode luminescent carbon dots as well as preparation method and application thereof

    CN113185972A